2020
DOI: 10.3389/fimmu.2020.00814
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Cell Death Interactions in Pulmonary Infection: Host Modulation Versus Pathogen Manipulation

Abstract: In the context of pulmonary infection, both hosts and pathogens have evolved a multitude of mechanisms to regulate the process of host cell death. The host aims to rapidly induce an inflammatory response at the site of infection, promote pathogen clearance, quickly resolve inflammation, and return to tissue homeostasis. The appropriate modulation of cell death in respiratory epithelial cells and pulmonary immune cells is central in the execution of all these processes. Cell death can be either inflammatory or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 173 publications
(221 reference statements)
1
16
0
1
Order By: Relevance
“…Ku et al demonstrated that cell fusion acts as a damage-associated molecular pattern (DAMP), triggering the cGAS-STING pathway that leads to autophagic cell death [ 34 ]. The presence of bacterial effectors that manipulate cell death pathways has not been established but it is likely that they exist in some capacity, based on the successful intracellular lifestyle of Bpm and the wide array of weaponry the pathogen uses within the cell [ 43 ]. The shift from active to persister bacteria would shut down the cytoprotection and manipulation exhibited by Bpm and cause the MNGC to undergo cell death, creating foci of necrosis and inflammation, similar to those seen at the center of the mature granuloma-like lesions of chronic melioidosis patients.…”
Section: Role Of Mngcs In Diseasementioning
confidence: 99%
“…Ku et al demonstrated that cell fusion acts as a damage-associated molecular pattern (DAMP), triggering the cGAS-STING pathway that leads to autophagic cell death [ 34 ]. The presence of bacterial effectors that manipulate cell death pathways has not been established but it is likely that they exist in some capacity, based on the successful intracellular lifestyle of Bpm and the wide array of weaponry the pathogen uses within the cell [ 43 ]. The shift from active to persister bacteria would shut down the cytoprotection and manipulation exhibited by Bpm and cause the MNGC to undergo cell death, creating foci of necrosis and inflammation, similar to those seen at the center of the mature granuloma-like lesions of chronic melioidosis patients.…”
Section: Role Of Mngcs In Diseasementioning
confidence: 99%
“…PcpA (pneumococcal choline-binding protein A) may also play a certain role [ 10 ]. Recent studies also demonstrated the ability of the pathogen to induce apoptosis, necroptosis and pyroptosis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are numerous studies on the molecular biology of the microbiological agents causing pneumonia, defense mechanisms of the host [ 1 , 7 15 ] and the treatment of the disease, studies on the pathology, cause, course and epidemiology of lobar pneumonia are lacking since the middle of the 1970s. The objectives of this work were therefore to re-study the lung changes in lobar pneumonia in relation to the cause and duration of the disease in a large number of autopsies.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer, anoikis resistance characterizes cancer cell anchorageindependent growth and EMT, contributing to cancer cell invasion and metastasis (62,64,65). In inflammatory diseases, as cardiovascular (66), pulmonary (67) and skin (49) diseases, and diabetes-related cardiovascular complications and retinopathy (62), aberrant anoikis is involved in excessive cell death and tissue injury.…”
Section: Granzyme B and Perforin-dependent And/or Perforin-independenmentioning
confidence: 99%